2014
DOI: 10.1136/bmjopen-2013-004058
|View full text |Cite
|
Sign up to set email alerts
|

The independent associations of recorded crime and perceived safety with physical health in a nationally representative cross-sectional survey of men and women in New Zealand

Abstract: ObjectivesWe investigated associations of officially recorded crime and perceived neighbourhood safety with physical health, evaluating potential effect modification by gender.SettingNationally representative population-based survey in New Zealand.ParticipantsIndividual-level data from 6995 New Zealand General Social Survey (2010–2011) participants with complete data on physical health status, perceived neighbourhood safety, sociodemographic characteristics and smoking. Crime rate for each participant's home c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
4
27
1
Order By: Relevance
“…38 Another found that police-recorded crime in New Zealand was associated with worse health, but only for women. 39 In contrast to other studies, we did not find associations for any one particular gender overall, but rather for certain race groups in women. 35,39,40 This may be due to the diversity of our sample that is uncommon in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…38 Another found that police-recorded crime in New Zealand was associated with worse health, but only for women. 39 In contrast to other studies, we did not find associations for any one particular gender overall, but rather for certain race groups in women. 35,39,40 This may be due to the diversity of our sample that is uncommon in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Neither the perceived risk of crime nor the fear of crime—probable mediators of the environmental impacts of crime on behavior—necessarily correlates strongly with actual crime reported within a locality (54). It is plausible that these subjective factors are influenced more by visual stimuli, such as instances of malicious damage, which may go some way toward explaining the stronger associations with sitting time observed in our study (47). Our previous research indicated that increasing area-level crime rates are associated with an increased risk of psychological distress (55), which is strongly associated with perceptions of safety (56, 57).…”
Section: Discussionmentioning
confidence: 77%
“…The Medical Outcomes Study Physical Functioning Scale is a 10-item scale that covers a range of activities, from basic actions needed for day-to-day living (e.g., bathing) to more vigorous activities (e.g., climbing stairs). Separate analyses were conducted for men and women, as previous research has indicated that area-level crime might influence health differentially by sex (47). We acknowledge at the outset that while the sex indicator available in our data was time-invariant, this was a methodological limitation, as gender is socially constructed and reflects, to a potentially large extent, clusters of social determinants that can change over time (48).…”
Section: Methodsmentioning
confidence: 99%
“…Third, we would have preferred to include police crime registrations in addition to the reported crime we obtained from the survey data, but this information was not available at the postal code level. Official recorded crime rates and perceived crime are not strongly correlated (McGinn et al, 2008;Taylor and Shumaker, 1990) and may have a different impact on health (Lovasi et al, 2014;McGinn et al, 2008). Even though we controlled for individual differences in reported crime frequency by using ecometrics, including crime registries would have provided us with a more comprehensive measure of objective neighbourhood social safety.…”
Section: Discussionmentioning
confidence: 99%
“…One social characteristic that has received some attention in relation to health is the social safety of the neighbourhood. In some studies, social safety has been associated with depression and depressive symptoms and worse physical health, but the findings are inconclusive (Diez Roux and Mair, 2010;Lovasi et al, 2014;Polling et al, 2014;Lorenc et al, 2012).…”
Section: Introductionmentioning
confidence: 95%